Introduction, Lloyd Fernando's Green is the Colour - Quayum, Mohammad Abdul (Estate of Llyod Fernando, 2012)
The chapter introduces the author and his second novel, Green is the Colour (1993). It examines the various thematic and stylistic aspects of the novel, especially the author's vision for the newly independent Malaysia -- how Malaysia could form a national identity overcoming its current culturally fragmented state.